Overall indoor quality of a non-renewed secondary-school building. Issue 1 (March 2016) - Loreti, Lisa; Barbaresi, Luca; De Cesaris, Simona; Garai, Massimo
This work is the result of a field study about overall comfort aspects performed in a secondary-school building in the surroundings of Bologna during the winter season. The campaign aimed at describing overall comfort aspects of the school both from an objective and a subjective point of view, thus a questionnaire was administered to pupils during ongoing lessons to compare physical measurements and subjective responses. The monitored attributes and items concerned typical indoor quality aspects: acoustical, thermal, indoor air, and visual quality. As weak points emerged from the data analysis, possible solutions are illustrated, focusing on acoustics and optimizing effectiveness and cost.